AMELIORASI LAHAN PASANG SURUT TIPE C DENGAN PEMBERIAN KOTORAN AYAM DAN KAPUR UNTUK TANAMAN JAGUNG MANIS (ZEA MAYS SACCHARATA STURT) - Rosmimi '; Gunawan Tabrani; Suseno ' (Jurnal Sagu, 2003)
The major problems found In uUlization of tidal swamp land for farmland is the abundmicc of water, low salinityami pi 1 and relatively low organic compounds. Tliese problems can be coped with the ameliorations. Based onthis fact, the experiment was carried out to evaluate the effect of variou.s doses of manure and dolomite in thegrowth and production of sweet com in the tidal swamp land. ThLs experiment has been conducted in the InsitVillage, Tebing Tinggi Barat Sub District Bengkalis Regency using a randomized factorial block experimentParameters observed were wet-weight and dry-weight of sweet com plant, emergence time of anther and stigma(days), length of corncob (cm), diamctcrofcomcob(cm), and number oflincof corncob .Experimental resultsshow that treatment of tidal swamp land with manures significantly influenced the wct-wcight of sweet cornplants, enuTgence time of stigma, and length of conicob. Addition of some dolomite to the tidal swamp land andinteraction between manures and dolomite did not significantly influence all parameters observed duringexperimental periods.